A Comprehensive Planning Model for Long-Range Academic Strategies - Walters, A.; Mangold, J.; Haran, E. G. P. (Management Science, 1976)
In this paper we describe a multiperiod linear programming model designed to aid the administrator of a school in planning and decision-making for a five-year horizon. The technique of goal programming is employed to accommodate the multiplicity of goals and the marginal trade-offs inherent in such a process. The model includes faculty staffing goals, career constraints, teaching and course loads, tenure constraints and budget constraints. A weighted sum of the deviations from the staffing goals make up the objective function of the prototype model considered. Several methods of estimating the various parameters of the model are discussed, and the results of a small example are also discussed.